Penerapan Model Picture and Picture Dengan Media Audio Visual untuk Meningkatkan Kualitas Pembelajaran IPS - Marselia, Novi (Universitas Sebelas Maret, 2020)
The research aimed to increase social subject quality of third grade elementary school students through the application of picture and picture model using audio visual. The research was designed using classroom action research consisted of planning, action, observation, and reflection. The data was collected using test, observation, documentation, and learning log. The result of teacher skill in the first cycle scored 25 in good category. Cycle II scored 26 in good category. Cycle III scored 33 in excelent category. The results of cognitive learning classical completeness in the first cycle was 61%. The second cycle was 78%. The third cycle was 87%.The conclusion was the application of picture and picture model using audio visual improved the quality of learning including teacher skills and student learning outcomes.